الضـوابط الشرعية لـنوافذ المعاملات الإسلامية في البنوك الـتقليدية دور الـلجنة الاستشارية الشرعية في بنك بـوميبترا التجاري - مفتـاح, صالح; فريدة, معارفي (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
With the growth pace of the banking industry and the entry of banks conventional  in field of Islamic banking has established branches and windows of the transactions, the Islamic product launches Islamic banking, in order to acquire a share of the banking market and realize  additional profits, as well as attract a segment of customers who prefer transactions  that comply Shariah      Malaysia is considered as one of the Islamic countries in the Middle Asian, which had its political desire  and popular support large in the establishment of a banking system not usurious, where central bank issued a law which allows traditional banks to provide Islamic banking services through Islamic windows, which encouraged towards providing Islamic products alternative to Besides traditional products as an  integral system, The prominent commercial banks "Bank commercial Boumeptra" which was the world leader in business  in pairing   services between Islamic and  conventional banks which  serve the nature of a whole  Malaysian society.   مع نمو وتيرة الصناعة المصرفية ودخول البنوك التقليدية مجال العمل المصرفي الإسلامي قامت بإنشاء فروع ونوافذ للمعاملات الإسلامية، وطرح منتجات مصرفية إسلامية، بهدف الإستحواذ على حصة من السوق المصرفية وتحقيق أرباح إضافية، بالإضافة إلى جذب شريحة من العملاء ممن يُفضلون المعاملات المتوافقة وأحكام الشريعة الإسلامية.         وتعتبر ماليزيا من الدول الإسلامية في الشرق الآسيوي التي كانت لها إرادة سياسية ودعم شعبي كبير في إقامة نظام مصرفي لاربوي، حيث أصدر البنك المركزي قانون يسمح للبنوك التقليدية بتقديم خدمات مصرفية إسلامية عبر نوافذ إسلامية، وهو ما شجع الأفراد على الإقبال نحو تقديم منتجات إسلامية إلى جانب المنتجات التقليدية كنظام أصيل ومن أبرز البنوك التجارية "بنك بوميبترا التجاري" الذي كان له السبق والريادة في مزاوجة الأعمال المصرفية الإسلامية والتقليدية بما يخدم طبيعة المجتمع الماليزي ككل. الكلمات المفتاح: التحول المصرفي، البنوك التقليدية، الفروع والنوافذ الإسلامية، بنك بوميبترا التجاري، اللجنة الإستشارية الشرعية.